PENGARUH VALUE ADDED CAPITAL EMPLOYED DAN HUMAN CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mulianah Mulianah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
Effect of Value Added Capital Employed and Human Capital for Financial Performance in Banking Companies listed on the Stock Exchange Indonseia. This study aimed to analyze the effect of value added capital employed and value added human capital on financial performance. The research data was obtained from the documentation that the company's financial statements to be sampled with the following criteria: banking companies listed in Indonesia Stock Exchange since 2009, and published financial statements for two consecutive years (2009 and 2010). The number of samples in this study were as many as 26 companies. This study uses multiple linear regression analysis, which is preceded by the analysis of the classical assumption, normality test, multicollinearity, and autocorrelation test, as well as heteroscedasticity test. Based on the results of the analysis can be concluded That Value Added Capital Employed variables not significant effect on financial performance. The magnitude of the effect of variable Value Added Capital Employed on the financial performance of 25.6% with a significance level of 0.081. while the variable Human Capital Value Added a significant negative effect on financial performance. The magnitude of the effect of variable Value Added Human Capital on the financial performance was 79.7% with a significance level of 0.037.